EP233/#541 Patterns of initial ovarian cancer recurrence on niraparib maintenance monotherapy in patients with no baseline evidence of disease following first-line chemotherapy: PRIMA/ENGOT-ov26/GOG-3012 post-hoc subgroup analysis. (4th December 2022) - Kamavra, M; Gonzalez-Martin, Antonio; Pothuri, Bhavana; Vergote, Ignace; Graybill, Whitney S; Mirza, Mansoor; Mccormick, Colleen; Lorusso, D; Freyer, G; O'Malley, David; York, Whitney; Malinowska, Izabela A; et al.
Abstract : Objectives: Patterns of recurrence on PARP inhibitor maintenance therapy are unclear and may affect treatment choices for subsequent therapy, including secondary cytoreductive surgery (SCS). This analysis of PRIMA/ENGOT-OV26/GOG-3012 evaluated patterns of recurrence on niraparib maintenance therapy. Methods: This post hoc subgroup analysis included 314 patients treated with niraparib maintenance monotherapy following first-line chemotherapy and who had no lesions identified by CT/MRI (or by investigator assessment) at baseline. Number and site(s) of initial recurrent lesions at the time of investigator-assessed RECIST-defined progressive disease (PD) were evaluated. Results: As of the primary data cut, May 17, 2019, with a median follow-up of 13.8 months (range <1–28), 141/314 (45%) patients developed investigator-assessed PD, with an average 1.9 (standard deviation 0.9) lesions at PD. At the time of recurrence, 62 patients (44%) had 1 lesion, 46 (33%) had 2 lesions, 24 (17%) had 3 lesions, and 9 (6%) had 4–5 lesions. The five most common sites with ≥1 lesion at PD were the peritoneum (n=45), lymph nodes (n=36), liver (n=34), other (n=26), and pelvis (n=20). Conclusions: For patients who received niraparib maintenance monotherapy after first-line chemotherapy and had no lesions at baseline, <50% had recurrent disease after a median 13.8 months of follow-up and >75% of patients with recurrence progressed in 1–2 sites. Prospective evaluation is required to determine whether patients with oligoprogressive disease have improved outcomes with local therapies, like SCS, in addition to systemic therapy. Funding: GSK (NCT02655016 ). Editorial support provided by Fishawack Health, funded by GSK.